2018
DOI: 10.3892/ijmm.2018.3707
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of TLR4 expression mediates the attenuating effect of erythropoietin on inflammation and myocardial fibrosis in rat heart

Abstract: The mechanism underlying the anti-inflammatory or antifibrotic activity of erythropoietin (EPO) in myocardial fibrosis (MF) remains elusive. In the current study, abdominal aortic constriction (AAC) was performed on rats and EPO and/or Toll-like receptor (TLR)4 were overexpressed in rat hearts through intramyocardial administration of lentivirus expressing the EPO and TLR4 genes. Hematoxylin and eosin staining and Masson's trichrome staining were performed on tissue sections from rat hearts for histopathologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 38 publications
0
15
0
1
Order By: Relevance
“…The underlying mechanisms that involved with IL‐6 signalling in HHD were yet to be disambiguated because of the complicated networks comprised of multiple biological process. It has been reported that the expression of IL‐6 is in positive correlation with that of MMP2 in several types of cardiovascular diseases such as aortic dissection, lipopolysaccharide‐induced cardiac fibrosis and pressure overload‐associated cardiac extracellular matrix (ECM) remodelling . In addition to the fact that an IL‐6 dependent increase of MMP2 and a MMP2‐dependent increase in IL‐6 are observed, STAT3 directly binds to the promoter of MMP2 to regulate cellular biological process .…”
Section: Discussionmentioning
confidence: 99%
“…The underlying mechanisms that involved with IL‐6 signalling in HHD were yet to be disambiguated because of the complicated networks comprised of multiple biological process. It has been reported that the expression of IL‐6 is in positive correlation with that of MMP2 in several types of cardiovascular diseases such as aortic dissection, lipopolysaccharide‐induced cardiac fibrosis and pressure overload‐associated cardiac extracellular matrix (ECM) remodelling . In addition to the fact that an IL‐6 dependent increase of MMP2 and a MMP2‐dependent increase in IL‐6 are observed, STAT3 directly binds to the promoter of MMP2 to regulate cellular biological process .…”
Section: Discussionmentioning
confidence: 99%
“…However, a series of studies have shown that indications benefiting from EPO treatment are clearly beyond the scope of anemia. In a variety of animal models, EPO exhibits multiple protective effects on tissues or organs, such as the pleiotropic effects on the cardiovascular system and kidney [7][8][9][10]. In preliminary experiment, we have observed that EPO could effectively improve the renal injury induced by cyclosporine A in rats.…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with a protective role for PI3K/Akt pathway, it is evident that the activation of the PI3K/Akt pathway is considered as a negative feedback regulator of TLR4 signaling in cardiac inflammation to control and limit the pro-inflammatory process (65,69,77,88). More recently, it was shown that erythropoietin exerts a protective role in myocardial fibrosis and cardiac hypertrophy, and the mechanism is associated with downregulating TLR4 expression by activating the PI3K/Akt signaling pathway (89). Notably, PI3K/Akt signaling also adversely affects the heart, possibly through the activation of PI3K different isoforms (p110α, p110γ).…”
Section: Tlr4/myd88/pi3k/akt Pathwaymentioning
confidence: 80%